Crustacean shell-based biosorption water remediation platforms: Status and perspectives. (1st February 2019) - Londono-Zuluaga, Carolina; Jameel, Hasan; Gonzalez, Ronalds W.; Lucia, Lucian
Abstract: The importance of water pollutants on human health has been the subject of intense study and constitutes perhaps the most significant grand challenge for the future of human society. Water remediation faces many challenges in effectively combating pollution, especially for low income populations where poor water sanitation and little to no access to technically competent and cost effective remediation are nearly insurmountable issues. In an effort to provide low-cost adsorbents, research over the last few years has focused on biological residual materials from plants and animal biomass to not only to add value, but to remediate water at a lower cost with the same or improved efficiency as commercially available option. Crustacean shells are among a class of biological residues that are commonly treated as a waste product of the sea food industry. However, potential valorization by remediation of heavy metal ions, organic matter, and anionic species is a topic of high interest in the current eco-friendly environment. The aim of this review is to provide insight on the state of the art of crustacean shells for addressing water remediation and to offer some perspective regarding challenges and the future of this type of biomass. Highlights: Water remediation is one of the biggest challenges facing the health and future well-being of our global population. Biosorption is a versatile, flexible cost-effective process. Biosorption needs to be explored to overcome barriers associated with technical feasibility and potential as a competitor to synthetic adsorbents in the market. The proposed review article is focused on providing a state-of-the-art for crustacean shells for biosorbent materials.